Proposal for an International Molybdenum Isotope Measurement Standard and Data Representation. Issue 2 (2nd January 2014) - Nägler, Thomas F.; Anbar, Ariel D.; Archer, Corey; Goldberg, Tatiana; Gordon, Gwyneth W.; Greber, Nicolas D.; Siebert, Christopher; Sohrin, Yoshiki; Vance, Derek
<x xml:space="preserve">Abstract</x> Molybdenum isotopes are increasingly widely applied in Earth Sciences. They are primarily used to investigate the oxygenation of Earth's ocean and atmosphere. However, more and more fields of application are being developed, such as magmatic and hydrothermal processes, planetary sciences or the tracking of environmental pollution. Here, we present a proposal for a unifying presentation of Mo isotope ratios in the studies of mass‐dependent isotope fractionation. We suggest that the δ98/95Mo of the NIST SRM 3134 be defined as +0.25‰. The rationale is that the vast majority of published data are presented relative to reference materials that are similar, but not identical, and that are all slightly lighter than NIST SRM 3134. Our proposed data presentation allows a direct first‐order comparison of almost all old data with future work while referring to an international measurement standard. In particular, canonical δ98/95Mo values such as +2.3‰ for seawater and −0.7‰ for marine Fe–Mn precipitates can be kept for discussion. As recent publications show that the ocean molybdenum isotope signature is homogeneous, the IAPSO ocean water standard or any other open ocean water sample is suggested as a secondary measurement standard, with a defined δ98/95Mo value of +2.34 ± 0.10‰ (2s).